Persistence of residues after endodontic retreatment related to the obturation technique and to the solvent - Aranda-Garcia, Arturo J. [UNESP]; Kuga, Milton C. [UNESP]; Vázquez-Garcia, Fernando A [UNESP]; Tonetto, Mateus R.; Bandeca, Matheus C.; Lima, Suellen N. L.; Freitas, Joana; Borges, Alvaro H.; Jordão-Basso, Keren C. F. [UNESP]; do Carmo Monteiro, Jardel C. (Jaypee Brothers Medical Publishing, 2017)
Objective: To quantify the persistence of residues after endodontic retreatment related to the root canal obturation technique (lateral compaction or single cone) previously performed and the solvent used (xylol or Endosolv-R) in the cervical and root apical segment using digital radiograph. Materials and methods: Forty root canals were prepared using the F2 instrument and filled with gutta-percha and AH Plus, 20 canals using #25 point by lateral compaction and the other 20 using F2 point by single cone. The root canals were transversely sectioned, and two segments (cervical and apical) were obtained. Radiographs were taken from the segment in buccolingual and mesiodistal direction, as well as the area that was originally filled with the root canal obturation was measured using ImageJ. After the specimens were set on special devices, the obturations were removed using the rotary system and divided into four groups (n = 10): G1 – lateral compaction and xylol; G2 – lateral compaction and Endosolv-R; G3 – single cone and xylol; and G4 – single cone and Endosolv-R. A new radiograph was taken and the area occupied by residues was measured. The persistence of residues was obtained from the obturation remaining in the root canal in percentage. The data were analyzed using Kruskal–Wallis test (p = 0.05). Results: There was no difference among the examined groups, regardless of the radicular segment or the radiograph direction (p > 0.05). Conclusion: The endodontic retreatment using xylol or Endosolv-R in the obturations previously performed by lateral compaction or single cone technique presented similar persistence of residues in the root canal, regardless of the radicular segment.
Keywords: Endodontic; Retreatment; Root canal; Rotary Instruments; Solvents